Coxiella burnetii shedding and serological status in pregnant and postpartum ewes - Trujillo, Mayra; Conan, Anne; Calchi, Ana Cláudia [UNESP]; Mertens-Scholtz, Katja; Becker, Anne AMJ; Gallagher, Christa; Mau, Alex; Marchi, Silvia; Machado, Marcus; André, Marcos Rogério [UNESP]; Chapwanya, Aspinas; Müller, Ananda (Elsevier, 2023)
This study aimed to evaluate the occurence C. burnetii-DNA shedding by pregnant (vaginal mucus and feces) and postpartum (vaginal mucus, feces and milk) meat breed ewes from Saint Kitts. Additionally, antibodies anti-C. burnetii were detected in serum, and milk. Barbados Blackbelly ewes (n=187) were sampled using stratified convenience cross-sectional sampling. There were two animal groups: pregnant (n=96) and postpartum (n=91). Vaginal mucus (n=187), feces (n=177) and milk (n=83) samples were subjected to a TaqMan real time qPCR assay for C. burnetii based on the IS1111 multi copy element. IgG antibodies against C. burnetii were tested in blood serum (n=187) and milk (n=61) samples, via indirect ELISA. McNemar and Fischer exact tests were used to compare occurrence between routes and between groups, respectively. Overall, 86.6% of all the animals (162/187) were shedding C. burnetti DNA through at least one route (vaginal and/or fecal and/or milk). The DNA shedding occurrence via vaginal (73% vs 51%, p-value=0.003) and fecal routes (64% vs 47%, p-value=0.001) was higher in the pregnant compared to the postpartum animals. There was no prevalent shedding route among vaginal, fecal or milk in all ewes. Overall, 38% of the ewes were seropositive for C. burnetii IgG and a total of 19.7% of the tested postpartum ewes had IgG antibodies in milk. The vaginal and fecal DNA shedding were not associated with the blood serology, nor was milk DNA shedding related to the milk serology status, thus there was no association between C. burnetii seropositivity and bacterial DNA shedding. In short, high occurrence of C. burnetii DNA shedding was observed within ewes in St. Kitts, and represents the first detection of the Q fever agent within the Caribbean islands. Bacterial shedding was more prevalent in pregnant ewes, highlighting the importance of gestating animals as a source of C. burnetii.
Keywords: bacterial shedding; Coxiellosis; PCR; Q fever; Serology; sheep